(untitled) (Northern International Medical College Journal, 2025)
Background: Metabolic acidosis is a frequent biochemical abnormality in critically ill neonates, often contributing to poor clinical outcomes. The corrected anion gap (cAG) serves as a valuable marker for unmeasured anions and acid-base disturbances, yet its role in predicting mortality and mechanical ventilation requirement in neonates remains underexplored. This study aimed to assess the prognostic significance of cAG in critically ill neonates with metabolic acidosis. Methods: This prospective observational study was conducted at Bangladesh Shishu Hospital & Institute (BSH&I) from July 2021 to June 2023, including 115 critically ill neonates with metabolic acidosis admitted to the NICU. Clinical and biochemical data were collected, including pH, bicarbonate, sodium, anion gap (AG), corrected anion gap (cAG), and base excess. Neonates were categorized into survivors (n=64) and non-survivors (n=51). Statistical analyses, including Pearson’s correlation, Student’s t-test, chi-square test, and logistic regression, were performed using SPSS version 22.0, with p < 0.05 considered statistically significant. Results: The mean cAG was significantly higher in non-survivors (31.53 mEq/L) compared to survivors (18.60 mEq/L) (p = 0.001). Severe metabolic acidosis (lower pH and bicarbonate, higher AG and cAG) was strongly associated with increased mortality. Mechanical ventilation was required in 90.6% of non-survivors, reinforcing its role as a predictor of poor outcomes. A strong negative correlation was observed between cAG and mechanical ventilation requirement (r= -0.607, p = 0.001). Additionally, a weak but statistically significant negative correlation between cAG and NICU length of stay (r = -0.213, p = 0.023) suggested that higher cAG values were associated with shorter LOS due to increased mortality. Conclusion: cAG is a strong predictor of mortality and mechanical ventilation requirement in critically ill neonates with metabolic acidosis. The severity of metabolic acidosis, as indicated by lower pH, bicarbonate levels, and elevated AG and cAG, was significantly associated with poor outcomes. Routine monitoring of cAG in NICU settings could serve as a valuable tool for early risk stratification and clinical decision-making. Northern International Medical College Journal Vol. 16 No. 1-2 July 2024-January 2025, Page 728-733